Ease of use, user satisfaction, and net benefits: evidence from digital customs platforms in free trade zones - Adhi Prasetio; Adriansyah Adriansyah (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
The digital transformation implemented by the Directorate General of Customs and Excise (DGCE) through the adoption of CEISA 4.0 aims to enhance efficiency, responsiveness, and reliability in customs services, including at operational units within the Free Trade Zone (FTZ). However, recurring issues such as system downtime, document validation failures, and access difficulties indicate a gap between user expectations and the net benefit of the system. This study aims to analyze the influence of perceived ease of use on user satisfaction and the net benefit of the CEISA 4.0 application among service users in the FTZ. A quantitative approach was employed using PLS-SEM via SmartPLS v4.2.9. A purposive sampling technique was applied to CEISA 4.0 service users in the FTZ areas of Batam, Bintan, Karimun, and Sabang. All constructs demonstrated adequate reliability and validity (Cronbach's Alpha 0.847–0.931; Composite Reliability 0.897–0.946; AVE 0.686–0.748). Data were collected through a Likert 1–5 scale questionnaire distributed to CEISA 4.0 service users in the Free Trade Zone. The theoretical framework integrates the Technology Acceptance Model (TAM) and the DeLone & McLean IS Success Model. Results indicate that: (1) perceived ease of use has a significant positive effect on user satisfaction (β = 0.649; p < 0.05); (2) user satisfaction has a significant positive effect on net benefit (β = 0.442; p < 0.05); (3) perceived ease of use has a direct significant positive effect on net benefit (β = 0.229; p < 0.05); and (4) user satisfaction significantly mediates the effect of perceived ease of use on net benefit (β = 0.287; p < 0.05). These findings underscore that improving ease of use of CEISA 4.0 is a strategic key to enhancing user satisfaction and net benefit of digital customs services in FTZ.